Model of Independency Mother in Caring for Preterm Infant based on Experiential Learning Care (ELC) - Noer Saudah; Nursalam Nursalam; Meriana Meriana; Agus Sulistyono (International Journal of Evaluation and Research in Education (IJERE), 2015)
The role of parents have done less during the preterm infant care in hospitals caused dependence in caring for the baby. The Obyective of the study was to development a model of independence of the mother in the care of preterm infants with experiential learning approach based theory of goal attainment. Research’s design used analytic correlational in stage 1 and stage 2 used quasy experimental. The population used all mothers with preterm infants treated in perinatal dr. Wahidin Sudiro Husodo Mojokerto and Prof. Dr Soekandar Mojokerto Hospital  with sample size was 28 samples respectively in the treatment group and the control group.Variables used knowledge, decision, action, interaction, experiential learning, and mother independence.The instrumen used questionnaire and checklist. The sample was selected by consecutive sampling method. The study was conducted in August to Desember 2014. In the treatment group was given ELC module and the control group was given treatment by leaflets.Technical data analysts used Partial Linear Square (PLS) and independent t-test. Knowledge maternal of preterm infants was influenced  on the increase interaction with λ = 0,167. Decision mother in caring for preterm infants have a significant effect on the improvement of maternal interaction with the nurse with a value λ = 0,664. Measures mother caring for preterm infants have a significant effect on the improvement of maternal interaction with the nurse with a value λ = 0,172. Interaction significant effect on the increase of Experiential Learning mother in caring for preterm infants with a value λ = 0,790. Experiential Learning significant effect on the increase of the independence of mothers caring for preterm infants with a valuei λ = 0,560. Maternal interaction with nurses significant effect on the improvement of maternal autonomy treating preterm infants with a value  λ = 0,204. T-test showed a significant difference between treatment groups increase independence and control groups. New finding of study is interaction with the approach of Experiential Learning Care (ELC) through methods role play a stronger in improving the independence than  interaction direct to independence. Independence of the mother in caring of preterm infants used nursing interventions in the form of Experiential Learning Care (ELC) more meaningful improvement when compared to the conventional models of intervention. The presence of mothers in the intervention process would trigger a thought process and raises awareness. Awareness will be reflected in the thought process and used as a foothold in the act and acquire new skills to be able to solve the problem. Experiential Learning Care (ELC) can increase the independence of the mother in  caring of preterm infants.